Psychological stress of ICU nurses in the time of COVID-19 - Shen, Xin; Zou, Xiaoyue; Zhong, Xiaofeng; Yan, Jing; Li, Li (Critical care (London, England), 2020)
[...]extreme incidents have occurred, such as suicide of nurses caring for critically ill patients, in Italy. If these psychological problems are not solved effectively, they may not only lead to a decline in their immunity and increase the chances of COVID-19 infection but also have an adverse impact on the quality and safety of the medical care system [2,3,4]. [...]early measures were actively taken, and the following improvements were made (Table 1): 1. [...]it is recommended to address the psychological problems of ICU nurses who care for patients with COVID-19 and take action as soon as possible to relieve the psychological pressure on these nurses.